Online food delivery - easy access to food/meal order vs. limited access to food information - Agnieszka GÓRKA-CHOWANIEC; Magdalena NIEWCZAS-DOBROWOLSKA (Communications of International Proceedings, 2024)
Online food delivery (OFD) platforms are very popular. More and more consumers use them to order meals. The market of OFD is growing very fast. It is a very comfortable way of ordering food and offers access to many restaurants at the same time. However, important disadvantages were identified about the access to food information. Five most popular OFD platforms in Poland were chosen and three most popular meals. Then the access to basic food information was revised (firstly allergens as it is a legal requirement and also ingredients or nutritional value). Lack of information was indicated for each platform and meal. On the basis of the legal requirements of food labelling and the revision of the OFD platforms offers of the most popular meals in Poland, it was shown that there is a big gap in the full access to food information. OFD platforms inform only about the food allergens or do not include any information about them. Consumer also do not have access to the full list of ingredients or the nutritional value. It shows the lack of equal access to food information to consumers who order meals in this way, and also may cause some health problems. These health problems may by caused by the consumption of food containing allergens without knowing about it and also by the highest than accepted fat or salt daily intake.
Keywords: OFD (online food delivery); food; consumer; food information; allergens.